IMPACT OF FAMILY FOOD SECURITY MANAGEMENT INTERVENTION ON STUNTING INCIDENCE IN KUPANG DISTRICT, NUSA TENGGARA TIMUR - Rahel Rara Woda (Universitas Nusa Cendana, 2026)
Stunting is one of the most common deficient conditions, estimated to have covered 800 million people worldwide, and 85% of children in the world are stunted and live in 20 countries (UNICEF, 2012). In Indonesia, the estimated prevalence of short and very short toddlers (stunting) is 36.8% (Riskesdas 2007) and as much as 37% (UNICEF, 2010). East Nusa Tenggara Province (NTT) is a province that has a prevalence above the national prevalence, namely 47-58.4%. Stunting can be influenced by various factors directly intake and infectious diseases and indirectly factors of mother's education, upbringing, mother's knowledge, provision of complementary foods, history of low birth weight babies, sanitation, and family socioeconomic status. Stunting results in stunted growth and development of children, including suboptimal brain growth, causing a decrease in IQ and intelligence. Based on Riskesdas 2007, 2010 and 2013 data, it shows that the incidence of stunting in NTT and in 2014 data for Kupang Regency there were 2630 children who were stunted and 1121 children with severe stunting. Seeing this incident and based on the fact that malnutrition in the golden age of toddlers is irreversible, it is deemed necessary for various parties to take preventive measures to control stunting. Intervention is a way to prevent and reduce the incidence of stunting while at the same time having a positive influence on behavior and eating habits, food supply in the household and other factors that aim to improve nutritional status. Researchers and the team conducted this research to find out and analyze the Impact of Family Food Security Management Pattern Interventions on Stunting Incidents in Kupang Regency, East Nusa Tenggara. To answer the objectives, this research was carried out using the pre-experimental method using the one group pre test post test only design. This design does not have a comparison group (control) but makes comparative observations before and after the intervention. The results obtained for 84 stunted children from 79 households show that mentoring, training and use of the land around the house as a vegetable garden and the existence of a fish pond provided to be managed by each household have a significant effect on the incidence of stunting. Which means that there is a decrease in the stunting rate in households that own and use vegetable gardens and fish ponds as a source of food for stunted children (sig = 0.010 where <0.05).